Flow photomicroreactor coated with monometal containing TiO2 using sonication: A versatile tool for visible light oxidation - Swaraj R. Pradhan (Elsevier, 2022)
Ultrasonication was used for deposition of synthesized Metal-TiO2 in the wall of a microtube. A detailed investigation of the photocatalytic activity was made by varying the atomic percentage of metals doped in TiO2. The sol-gel synthesized materials were analyzed by various techniques like X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), etc. The photocatalytic activities of the monometallic TiO2 fluoropolymer-based microreactors were evaluated for the oxidation of benzyl alcohol in flow. Microflow photocatalytic oxidation tests proved that the Fe-TiO2 material has the highest photocatalytic conversion of benzyl alcohol compared with the other titania samples under UV and visible light irradiation.